Concentração dos ácidos graxos polinsaturados no leite de mulheres doadoras antes e após suplementação com linhaça ou ômega-3 - Silva, Lucieni Cristina (2014)
Human breast milk is a source of polyunsaturated fatty acids (PUFA), which are considered essential during the prenatal period and the complete biochemical development of the brain and retina period that occurs around the age of two and of which are accumulated throughout child hood. Among these fatty acids, the family of omega-3 and omega-6 stand out for their direct neurological and immunological action. Objective: To assess and compare the serum levels of docosahexaenoic acid and eicosapentaenoic acid in breast milk of women before and after supplementation with omega-3 of animal origin (fish oil capsules) or of vegetable origin (golden flaxseed meal). Methods: Upon review of the milk bank records, lactating mothers were divided into three groups: Group (GI) 20 lactating mothers without change in dietary habits; Group (GII) 20 lactating mothers who received 30 envelopes (15g/per unit) of golden flaxseed meal and Group (GIII) 20 lactating mothers who received 30 capsules of fish oil. Through the gas chromatographic method, in 56 milk samples, offered element and its metabolites were quantified (four samples were discarded because they do not contain sufficient content for playback in the chromatograph column).Results: After the supplementation of the lactating women, a significant difference between the groups in relation to the concentration of the fatty acid precursor of the omega-3 series alpha-linoleic(p =0.01) was observed, with the highest concentrations observed in the flaxseed-supplemented group compared to the control group(p <0.05). The EPA and DHA fatty acids analyzed in breast milk of participants in the before moment alsos howed different concentrations between groups (p =0.002; 0.01, respectively). In particular analysis of each group(intragroup), lactating mothers of the flaxseed group showed significant increase in the concentrations of the fatty acid alpha-linolenic after supplementation(p =0.02). There was no significant difference between the concentrations of other fatty acids measured before and after supplementation of lactating women. Conclusion: The beneficial effects of PUFA are evident in the lactation stage. The mother has the responsibility to offer her child the necessary nutrients for its development. Promoting actions that encourage breastfeeding and suggesting changes in eating habits can be a major contributing factor in reducing there are of disabling diseases in fetal and neonatal periods.